Survey on Training Satisfaction among German Neurosurgical Trainees - Lawson McLean, Anna Cecilia; Maurer, Stefanie; Nistor-Gallo, Dorothea; Moritz, Ina; Tourbier, Meriem (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Background There has been a fivefold increase of neurosurgeons over the last three decades in Germany, despite a lesser increase in operations. Currently, there are approximately 1,000 neurosurgical residents employed at training hospitals. Little is known about the overall training experience and career opportunities for these trainees. Methods In our role as resident representatives, we implemented a mailing list for interested German neurosurgical trainees. Thereafter, we created a survey including 25 items to assess the trainees' satisfaction with their training and their perceived career prospects, which we then distributed through the mailing list. The survey was open from April 1 until May 31 2021. Results Ninety trainees were enrolled in the mailing list and we received 81 completed responses to our survey. Overall, 47% of the trainees were very dissatisfied or dissatisfied with their training. Sixty-two percent of the trainees reported a lack of surgical training. Fifty-eight percent of trainees found it difficult to attend courses or classes and only 16% had consistent mentoring. There was an expressed desire for a more structured training program and mentoring projects. In addition, 88% of trainees were willing to relocate for fellowships outside their current hospitals. Conclusions Half of the responders were dissatisfied with their neurosurgical training. There are various aspects that require improvement, such as the training curriculum, structured mentoring, and reduction of the amount of administrative work. We propose the implementation of a modernized structured curriculum, which addresses the mentioned aspects, in order to improve neurosurgical training and, consecutively, patient care.
CRIS-Team Scopus Importer:2024-12-16
Keywords: curriculum; Germany; neurosurgical training; residency training